Extended Visualization for a Digital Journal - Narayanan, A/L N. Kulathu Ramaiyer; Muhammad Salman, Khan; Muhammad Tanvir, Afzal; Hermann, Maurer (2009)
Content analysis has been a tradition of many electronic and printed journals, in order to ensure quality and the journal’s standing. Traditionally, researchers have tried to analyze patterns in scholarly publications using normal tables and statistical charts. In this paper we present an interactive visualization system that can help for a deeper analysis of different trends’ patterns hidden in scholarly publications of a digital journal. We apply this technique to the Journal of Universal Computer Science (J.UCS). The proposed visualization system is an easy to use web application, based on animated 2D bubble chart and pie chart to handle geographical, temporal and large kinds of categorical data. The paper gives a brief overview of the state of the art visualization techniques available to understand the knowledge structure of any given academic discipline. The design and technical aspects of the proposed visualization tool and various interesting results drawn from it have been discussed.